The Role of Complementary and Alternative Medicine in Facial Plastic Surgery - Luu, Neil N.; Soldatova, Liuba; Friedman, Oren (Facial Plastic Surgery, 2021)
Complementary and alternative medicine (CAM) has become increasingly popular among facial plastic surgery patients. Over the last few decades, there has been a surge in the use of CAM. Despite the increasing prevalence of CAM, patients may feel uncomfortable discussing these therapies with their physicians, and physicians feel under-equipped to engage in meaningful discussions regarding these nontraditional therapies. This article reviews recent literature on the use of CAM for skin treatment in an attempt to provide additional resource. To date, the evidence to support statistically significant symptom improvement with use of non-traditional therapies remains limited. While preliminary data supports essential oil therapy in some cases, the results of the studies investigating other CAM therapies (traditional Chinese medicine, Ayurveda, and homeopathy) have been mixed and inconclusive.
Keywords: complementary and alternative medicine; skin care; facial plastic